Mastering Strategic Management - Edwards, Janice; Ketchen, Dave; Short, Jeremy (Open textbook library., 2014)
Mastering Strategic Management is designed to enhance student engagement in three innovative ways. The first is through visual adaptations of the key content in the book. It is well documented that many of today's students are visual learners. To meet students' wants and needs (and thereby create a much better teaching experience for professors), Mastering Strategic Management contains multiple graphic concept pages in ever section of every chapter of the book. Think of graphic concept pages as almost like info-graphics for key concepts in each section. This feature sets Mastering Strategic Management apart from any strategic management book on the market today. The second way the authors capture student interest through their textbook is by using a real-world company as the running example in each chapter. For example, Chapter 1 in Mastering Strategic Management utilizes Blackberry to harness the conceptual coverage of the chapter in a running, corporate, application to which students will relate. The third inventive way Mastering Strategic Management holds the attention of strategic management students is through the “strategy at the movies” feature in each chapter that links course concepts with a popular motion picture.